Use of Zirconia to Restore Severely Worn Dentition: A Case Report - Manish Agrawal; Banashree Sankeshwari; Channaveer V. Pattanshetti (Case Reports in Dentistry)
The management of tooth wear has been a subject of increasing interest from both preventive and restorative points of view. Severe tooth wear is frequently multifactorial and variable. Successful management is a subject of interest in dentistry. A critical aspect is to determine the occlusal vertical dimension (OVD) and a systematic approach that can lead to a predictable and favorable treatment prognosis. Management of patients with worn dentition is complex and difficult. Accurate clinical and radiographic examinations, a diagnostic wax-up, and determining OVD are crucial. This paper describes the full-mouth rehabilitation of a 47-year-old bruxer with a severely worn dentition.